South to America a journey below the Mason-Dixon to understand the soul of a nation - Perry, Imani 1972- (ECCO, An Imprint of HarperCollinsPublishers, 2022)
"An essential, surprising journey through the history, rituals, and landscapes of the American South--and a revelatory argument for why you must understand the South in order to understand America"--
Includes index
Keywords: Perry, Imani / 1972- / Travel / Southern States; Southern States / Description and travel; Southern States / Social life and customs / 21st century; Southern States / Race relations; HISTORY / Americas (North, Central, South, West Indies); Manners and customs; Race relations; Travel; Southern States; 2000-2099; Travel writing